2014
DOI: 10.5897/ajb2014.13838
|View full text |Cite
|
Sign up to set email alerts
|

Pigment production from a mangrove Penicillium

Abstract: A mangrove Penicillium producing red pigment was cultured in an optimized medium that was designed by the authors previously and used in this study. The purpose of this study was to identify the pigment and also to study the effect of bio elements on pigment production. Pigment from the medium was efficiently extracted using chloroform, ethyl acetate and n-butanol. Most of the red pigment was extracted into ethyl acetate and further purified by preparative thin layer chromatography. From 1 H and 13 C NMR data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Most of the strains were found to be pigment producers however special interest toward a red color directed further study on Penicillium, which was then interogatted for optimization of its media conditions and the effect of metals and salts on pigment yield. The main purpose of the study was to optimize the effect of various bioelements (Chintapenta et al, 2014) and it was shown that a higher concentration of salt has a negative effect on pigment yield. This is due to the fact that the presence of these electrolytes alter the pH of the medium and prevent diffusion of pigment.…”
Section: Mangrove Sedimentmentioning
confidence: 99%
“…Most of the strains were found to be pigment producers however special interest toward a red color directed further study on Penicillium, which was then interogatted for optimization of its media conditions and the effect of metals and salts on pigment yield. The main purpose of the study was to optimize the effect of various bioelements (Chintapenta et al, 2014) and it was shown that a higher concentration of salt has a negative effect on pigment yield. This is due to the fact that the presence of these electrolytes alter the pH of the medium and prevent diffusion of pigment.…”
Section: Mangrove Sedimentmentioning
confidence: 99%
“…The extraction of pigments was carried out according to the method. [27] After 20 days of incubation, biomass was removed by filtration through Whatman No. 1 filter paper and the broth containing the extracellular pigment/metabolites was obtained.…”
Section: Extraction Of Extracellular Pigments/metabolitesmentioning
confidence: 99%
“…1 filter paper and the broth containing the extracellular metabolites was obtained. The extraction of pigments was carried out according to the method described by Lathadevi et al [19]. The broth obtained was used for the extraction of the different compounds by separating funnel using different organic solvents from non-polar to polar (chloroform, ethyl acetate, n-butanol, and methanol) in the ratio of 1:1.…”
Section: Fermentation and Extractionmentioning
confidence: 99%